Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1038/oby.2003.207
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Body Fat from Anthropometry and Isotopic Dilution: A Four‐Country Comparison

Abstract: ECKHARDT, CARA L., LINDA S. ADAIR, BENJAMIN CABALLERO, JOSEPHINE AVILA, IGOR Y. KON, JINZHONG WANG, AND BARRY M. POPKIN. Estimating body fat from anthropometry and isotopic dilution: a fourcountry comparison. Obes Res. 2003;11:1553-1562. Objective: The goal was to assess the ability of BMI to predict body fat (BF) among youths in four countries and identify the degree to which additional anthropometric measures improve this prediction. BMI is widely recommended as an indicator of overweight. However, whether B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 33 publications
(43 reference statements)
1
13
1
4
Order By: Relevance
“…This same age range was studied in other investigations for the assessment of body composition in adolescents by BIA, anthropometry and DDM (12,23,28,29). In the present study, as in previous ones, no statistically significant difference in weight (P = 0.20) or BMI (P = 0.07) was observed between genders, results that allowed us to perform the analyses as a group instead of separating by gender.…”
Section: Discussionsupporting
confidence: 58%
“…This same age range was studied in other investigations for the assessment of body composition in adolescents by BIA, anthropometry and DDM (12,23,28,29). In the present study, as in previous ones, no statistically significant difference in weight (P = 0.20) or BMI (P = 0.07) was observed between genders, results that allowed us to perform the analyses as a group instead of separating by gender.…”
Section: Discussionsupporting
confidence: 58%
“…39 There are several established limitations in using BMI as a measure of obesity. 29,[40][41][42][43][44] First, BMI fails to differentiate between mass contributed by muscle and that by adipose tissue. Second, by dividing weight by the square of height, BMI has been criticized for inadequately adjusting for height and for being disparately associated with body proportions (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…As maturational state affects the composition of the FFM (Slaughter et al, 1988), correction for levels of maturation between children might have improved the accuracy of predicting Tanita system and skinfold thickness equations. However, Eckhardt et al (2003) reported that in Asian males (15.670.44 years), inclusion of maturation correction did not produce a more precise prediction of BF.…”
Section: Discussionmentioning
confidence: 99%